Guide to Canadian English usage - Fee, Margery; McAlpine, Janice (Oxford Univ. Press, 1997)
"Canadian English is a variety of English in its own right, with its own distinctive mix of features. Yet in the past Canadians wanting to find out about their language have often had to choose between British and American guides. The Guide to Canadian English Usage offers an alternative based on what Canadian writers (among them Margaret Atwood, Pierre Berton, Northrop Frye, Janice Kulyk Keefer, Robert Kroetsch, and Miriam Waddington) actually do." "Drawing on a corpus of 12 million words of Canadian English published in books, magazines, scholarly journals, and newspapers, its 1,750 entries provide comprehensive coverage of specifically Canadian questions as well as problems common to all English-speakers." "Each entry explains the problem at hand, outlines a range of prescriptions, and then either recommends a particular usage or reviews the alternatives from which the now-informed reader can choose. Quotations from a wide range of sources - including, in addition to the corpus, a further 650 million words of Canadian newspaper and magazine writing - illustrate both problems and solutions."--BOOK JACKET.